Question

Using undetermined coefficients superposition approach find the general solution for: y'' - y = e^(x) + 2x^(2) -5

Answer #1

Solve using undetermined coefficients - superposition
approach:
y" - 4y' + 5y = 6cos(x) + 7sin(x)

X'= 6x-5y+e^5t
Y'= x+4y
Find the general solution using undetermined coefficients

Solve by undetermined coefficients (superposition approach)
y''- 4y'+4y = e^(4x)+xe^(-2x)
y(0) = 1
y'(0)= -1

Find the general solution of the equation using the method of
undetermined coefficients: y''-y'=5sin(2x)

Use the method of Undetermined Coefficients to find the general
solution
y'' - y' -2y = e^(2x)

Non homogeneous eq w constant; undetermined coefficients
Find the general solution:
1) y" + 4y' + 4y = xe^−x.
2) y" + 2y' + 5y = e^2x cos x.
Determine a suitable form for a particular solution z = z(x) of
the given equations
1) y" + 2y' = 2x + x^2e^−3x + sin 2x.
2) y" − 5y' + 6y = 2e^2x cos x − 3xe^3x + 5.
3) y" + 5y' + 6y = 2e^2x cos x −...

Find the general solution of y'' − 2y' = sin(5x) using the
method of undetermined coefficients

find a general solution using the method of undetermined
coefficients for a given differential equation.
y'=[-3 1; 1 -3]y+[-6 2]e^-2t
Please explain it as easily as possible.
Please write so that I can read your handwriting.

y''+y=5cost-sint
use undetermined coefficients to find the general solution

Solve for undetermined coefficients:
y'''-y''-4y'+4y=5 - e^x +e^2x

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 7 minutes ago

asked 37 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago

asked 2 hours ago

asked 2 hours ago

asked 2 hours ago

asked 2 hours ago

asked 2 hours ago